Neurological Outcome of Early versus Late Surgery Following Cervical Spinal Cord Injury - Kafle, P.; Chaudhary, P. K.; Thapa, J.; Sharma, M. R. (Kathmandu University Medical Journal, 2022)
Background There are numerous retrospective studies and a few prospective studies to determine the neurologic outcome after early versus late surgical treatment for cervical spinal cord injury. Objective To compare the neurological outcome between early (within 72 hours after injury) and delayed (≥ 72 hours after injury) surgery in patients with cervical spinal injury. Method This is a retrospective analysis of the neurological outcome of early versus late surgery following cervical spinal cord trauma. Patients meeting appropriate inclusion criteria were divided into an early or a late surgical treatment group. The neurologic outcomes and other complications were recorded up to six months of follow-up. Result Overall, there was a significant difference in neurological status at presentation and at follow-up (p < 0.001). However, there was no statistically significant difference between the early versus late surgery groups (p-value 0.261) in terms of neurological outcome. Complications were found to be higher among those undergoing posterior surgical approach (OR = 23.75; 95% CI 2.65, 212.98) than those with anterior or combined approach (p=0.005). However, multivariate analysis of these variables failed to show any statistically significant difference between the two groups. Conclusion The timing of surgery does not alter the neurological outcomes and the development of complications significantly. The American Spinal Cord Injury Association (ASIA) status at the time of presentation is found to be the single most important factor correlating with the neurological outcome.